BOLALARNING MUSTAQIL FIKRLASHINI RIVOJLANTIRISHDA PEDAGOGNING FAOLIYATI - Romanova, S.E. (SCIENCE and SOCIETY, 2024)
The content of the article is that a child’s ability to think in music education depends on his understanding, intelligence, intellect, as well as the environment, existing conditions, thinking is a variable mental quality, and in the process of its development it is described that it consists of two stages and its effective result.
Keywords: musical activity; thinking; art; talented youth; musical instrument; national property; circle work; creative abilities